Peripheral T-Cell Lymphoma in Mediastinum Lymph Nodes and Lung Associated to Histoplasmosis in a Patient with Chronic Lymphoid Leukemia/Small Lymphocytic Lymphoma - Oliveira, Cristiano Claudino [UNESP] (2017)
Sao Paulo State Univ, Botucatu Sch Med, Dept Pathol, Sao Paulo, Brazil